2017
DOI: 10.18632/oncotarget.15645
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of cyclin dependent kinase 9 inhibition in esophageal adenocarcinoma

Abstract: Role of cyclin dependent kinase 9(CDK9) as a potential target in esophageal adenocarcinoma (EAC) is unknown. We investigated CDK9 protein expression in EAC and Barrett's esophagus and role of CDK9 in oncogenic processes of EAC in vitro and in murine xenografts. The CDK9 expression was significantly higher in EAC as compared to Barrett's esophagus in patient samples. Stable shCDK9 in SKGT4 reduced proliferation by 37% at day 4, increased apoptosis at 48 hours and induced G1 cell cycle arrest at 48 hours (58.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Previously, we showed that CDK9 inhibitors exert dose-dependent anti-proliferative effects against 6 esophageal adenocarcinoma cell lines [16]. Radioresistant OE33R cells were established by exposing radiosensitive OE33 cells to weekly doses of 2 Gy radiation and radiation resistance was achieved after 45 fractions of 2 Gy radiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we showed that CDK9 inhibitors exert dose-dependent anti-proliferative effects against 6 esophageal adenocarcinoma cell lines [16]. Radioresistant OE33R cells were established by exposing radiosensitive OE33 cells to weekly doses of 2 Gy radiation and radiation resistance was achieved after 45 fractions of 2 Gy radiation.…”
Section: Resultsmentioning
confidence: 99%
“…BAY1143572 induces its anti-tumorigenic effects in adult T-cell leukemia/lymphoma by inhibiting pSer2 and pSer7 RNA Pol II, MYC, and MCL-1. Our studies [16] (unpublished data) indicate that CDK9/p-TEFb inhibition is the dominant mechanism of action for three CDK inhibitors: Flavopiridol [21, 22], CAN 508 and BAY1143572, in esophageal adenocarcinoma. In the present study, we show for the first time that inhibition of CDK9 potently enhances radiation sensitivity in various preclinical models of esophageal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CDK9 can be activated by four distinct cyclins (T1, T2a, T2b, and K) to form one of four positive transcription elongation factor (P-TEFb) complexes that regulate RNA polymerase II [10]. CDK9 is found to be overexpressed in a variety of cancers including pancreatic [11], ovarian [12], cervical [13], esophageal [14] and osteosarcoma [15], with increased CDK9 correlated to poorer patient prognosis [11,15,12]. From in vitro studies and animal models, CDK9 has been implicated as a potential target for therapeutic intervention due to its role in MYC stabilization [16], chemo-and radio-resistance [17][18][19], and maintenance of cancer cell stemness [20,21].…”
Section: Introductionmentioning
confidence: 99%